2014
DOI: 10.1093/jis/14.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs between survival, longevity, and reproduction, and variation of survival tolerance in Mediterranean Bemisia tabaci after temperature stress

Abstract: The invasive Mediterranean Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) has emerged as one of the most common agricultural pests in the world. In the present study, we examined the cross-tolerance, fitness costs, and benefits of thermal tolerance and the variation in the responses of life history traits after heat-shock selection. The results showed that survival and longevity of Mediterranean B. tabaci were decreased significantly after direct or cross temperature stress and that the number of eggs per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
(46 reference statements)
2
10
0
Order By: Relevance
“…Similarly, Cui et al (2008) showed that survival rates drop after brief exposure to higher temperatures (39 -45 °C), and B. tabaci MEAM1 is more thermotolerant than Trialeurodes vaporariorum (Westwood). A similar decline in survival after exposure to high temperatures was also reported for B. tabaci MED (Zhu et al 2010;Lü et al 2014a) and B. tabaci MEAM1 (Muñoz-Valencia et al 2013;Diaz et al 2015). Fecundity of whiteflies after brief exposure to heat shock generally reduces with temperature increase (Elbaz et al 2011;Xiao et al 2016).…”
Section: Life History Traitssupporting
confidence: 73%
See 1 more Smart Citation
“…Similarly, Cui et al (2008) showed that survival rates drop after brief exposure to higher temperatures (39 -45 °C), and B. tabaci MEAM1 is more thermotolerant than Trialeurodes vaporariorum (Westwood). A similar decline in survival after exposure to high temperatures was also reported for B. tabaci MED (Zhu et al 2010;Lü et al 2014a) and B. tabaci MEAM1 (Muñoz-Valencia et al 2013;Diaz et al 2015). Fecundity of whiteflies after brief exposure to heat shock generally reduces with temperature increase (Elbaz et al 2011;Xiao et al 2016).…”
Section: Life History Traitssupporting
confidence: 73%
“…Fecundity of whiteflies after brief exposure to heat shock generally reduces with temperature increase (Elbaz et al 2011;Xiao et al 2016). However, other studies have shown no significant effect (Cui et al 2008;Zhu et al 2010;Lü et al 2014a). Furthermore, progeny viability post-heat shock could either decrease (Cui et al 2008;Diaz et al 2015) or show an inconsistent pattern (Muñoz-Valencia et al 2013;Xiao et al 2016) with temperature increase.…”
Section: Life History Traitsmentioning
confidence: 98%
“…30% and 40% survival from egg to adult at 15 °C when reared on eggplant and bell pepper but no survival when reared on oriental melon 33 . Some attempts have also been made to examine the capacity of tolerance of the two species of whiteflies to sublethal high temperatures, and the data indicate that the two species could usually obtain some survival following a few hours exposure to temperatures in the range of 40–45 °C 34 35 36 37 . However, currently available case studies provide yet insufficient knowledge of the differences between MEAM1 and MED in their thermal tolerance, because in many cases the experiments were conducted on one of the two species at a time and due to the effects of various factors, such as differences of environmental variables other than temperature, data obtained by different authors may not be compared directly 34 36 .…”
mentioning
confidence: 99%
“…As an invasive species, MED has immense vast potential to adapt to a wide range of environmental temperatures 5153 , which allows it to successfully colonize and disperse after invasion and to occupy habitats in a wide latitude range. Previous studies 54 have found that MED can significantly improve its survival rate within two generations after heat shock selection experiments, indicating that the rapid increase in viability represents an important strategy for surviving harsh environments. These results illustrated that MED possessed a powerful regulatory plasticity system, along with a number of advantages over mammalian models including ethical acceptability, short generation times and the potential to investigate complex interacting parameters such as fecundity, longevity, gender ratio, and resistance to environmental stress, rendering it a suitable model for studying epigenetic adaptions.…”
Section: Introductionmentioning
confidence: 93%